2011
DOI: 10.1111/j.1442-2050.2010.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative interventions and prognosis in patients with advanced esophageal cancer

Abstract: In a retrospective review, in order to describe the palliative care and prognosis of patients with advanced cancer of the esophagus, the clinical characteristics and the treatment modalities applied were explored in relation to survival and symptom relief for 261 patients treated without curative potential. The data were obtained from a study of all patients with cancer of the esophagus treated at the Norwegian Radium Hospital in the 10-year period from 1990 to 1999. Medical data of the patients were reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…[20] Amdal et al reported that there was no difference in dysphagia relief between EBRT ± ILRT, ILRT alone, endoluminal stent, laser, chemotherapy and best supportive care. [21] 63% of our patients had dysphagia at presentation. In addition, there were a multitude of baseline symptoms including other loco-regional symptoms like cough, often with hemoptysis (30%), hoarseness (24%), chest pain (20%), vomiting and regurgitation (24%), back pain (27%) and painful lymph nodal swelling (4%).…”
Section: Resultsmentioning
confidence: 94%
“…[20] Amdal et al reported that there was no difference in dysphagia relief between EBRT ± ILRT, ILRT alone, endoluminal stent, laser, chemotherapy and best supportive care. [21] 63% of our patients had dysphagia at presentation. In addition, there were a multitude of baseline symptoms including other loco-regional symptoms like cough, often with hemoptysis (30%), hoarseness (24%), chest pain (20%), vomiting and regurgitation (24%), back pain (27%) and painful lymph nodal swelling (4%).…”
Section: Resultsmentioning
confidence: 94%
“…It is also used as palliative treatment for advanced oesophageal tumours that are not amendable to surgical resection (Da Silveira and Artifon , Amdal et al . ). Both procedures are regarded as safe with low complication rates.…”
Section: Discussionmentioning
confidence: 97%
“…The Nd:YAG laser is commonly used for the treatment of Barrett's oesophagus in humans, which is a premalignant metaplasia of the distal oesophageal epithelium (Gossner et al 2002, Schembre 2003. It is also used as palliative treatment for advanced oesophageal tumours that are not amendable to surgical resection (Da Silveira and Artifon 2008, Amdal et al 2011). Both procedures are regarded as safe with low complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several methods for this purpose, including the esophageal stent, endoscopic dilation, radiotherapy (both external and endoluminal—brachytherapy), chemotherapy and laser recanalization (YAG) [3]. The choice of procedure and the response to treatment should be properly related to life expectancy, which has also been related to performance status, weight loss, tumor extension, clinical stage, sex and age [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Most of these cancers are diagnosed at an advanced stage in patients with comorbidities. This factor prevents curative treatment in the majority of them, thus making palliative care a more realistic option [1, 3]. …”
Section: Introductionmentioning
confidence: 99%